2014
DOI: 10.1063/1.4854355
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of hydrogen configuration and its roles in SrTiO3−δ

Abstract: As a source of carrier electron, various configurations of hydrogen in SrTiO3 are searched by using first-principles calculations. The most stable form of hydrogen is found to be H−, where doubly charged oxygen vacancy $V_{\rm O}^{2+}$VO2+ changes into singly charged ${\rm H}_{\rm O}^+$HO+. Most importantly, an additional H− is found to be weakly trapped by ${\rm H}_{\rm O}^+$HO+, which completely neutralizes carrier electrons by forming ${\rm (2H)}_{\rm O}^0$(2H)O0. These unexpected behaviors of hydrogen, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 32 publications
4
33
0
Order By: Relevance
“…7,25 Thus, we assume that an electron spin and a Mu + donor are respectively located on a Ti site and an interstitial site near an oxygen ion to form an OMu − group in the same unit cell. Based on the atomic configuration around H + i reported from first-principles calculations, 11 Mu + i is expected to locate at θ = 29 • on a TiO 2 plane near an O-O edge of an oxygen octahedron ( Fig. 1(c)).…”
mentioning
confidence: 99%
“…7,25 Thus, we assume that an electron spin and a Mu + donor are respectively located on a Ti site and an interstitial site near an oxygen ion to form an OMu − group in the same unit cell. Based on the atomic configuration around H + i reported from first-principles calculations, 11 Mu + i is expected to locate at θ = 29 • on a TiO 2 plane near an O-O edge of an oxygen octahedron ( Fig. 1(c)).…”
mentioning
confidence: 99%
“…Several theoretical works have been published to date on the stability of hydrogen ions in oxygen-deficient perovskite titanates ATiO 3−δ and their transport and exchange mechanisms [4][5][6][7] . These studies commonly concluded that the most stable single hydrogen configuration in an n-type carrier-rich environment is H − at a doubly charged oxygen vacancy V 2+ O , formally expressed as H + O .…”
mentioning
confidence: 99%
“…This scenario explains the hydrogen transport and exchange abilities of ATiO 3−x H x well, without involving migration of the other heavy elements. Some calculations dealt with an interaction between an H + O center and an incoming H + i , which should be taken into account when considering hydrogen transport and exchange in highly hydrogenated ATiO 3−x H x 5,6 . Three metastable configurations were theoretically proposed for two hydrogen atoms at the insights into the mechanisms of hydrogen transport and exchange in ATiO 3−x H x are still quite limited.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…At the oxygen vacancy, hydrogen is expected to form a hydride ion (H − ). It has been suggested that a vacancy-hydrogen complex is formed with hydrogen negatively charged in SrTiO3 bulk experimentally [15,16] and theoretically [17]. Previous photoemission studies have shown that the in-gap state generated by ion bombardment or annealing on a SrTiO3(111) is decreased by H2 dosage [18,19].…”
Section: Introductionmentioning
confidence: 99%